Ultrafast iron-catalyzed reduction of functionalized ketones: highly enantioselective synthesis of halohydrines, oxaheterocycles, and aminoalcohols$ddedicated to Professor Dietmar Stalke on the occasion of his 60th birthday - Blasius, Clemens K.; Vasilenko, Vladislav; Gade, Lutz H. (Angewandte Chemie, 2018)
A molecularly defined chiral boxmi iron alkyl complex catalyzes the hydroboration of various functionalized ketones and provides the corresponding chiral halohydrines, oxaheterocycles (oxiranes, oxetanes, tetrahydrofurans, and dioxanes) and amino alcohols with excellent enantioselectivities (up to >99 %ee) and conversion efficiencies at low catalyst loadings (as low as 0.5 mol %). Turnover frequencies of greater than 40000 h−1 at −30 °C highlight the activity of this earth-abundant metal catalyst which tolerates a large number of functional groups.